2006
DOI: 10.1021/bi060355g
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Stability among the Transmembrane Helices of Lactose Permease

Abstract: Combining structure determinations from nuclear magnetic resonance (NMR) data and molecular dynamics simulations (MD) under the same environmental conditions revealed a startling asymmetry in the intrinsic conformational stability of secondary structure in the transmembrane domain of lactose permease (LacY). Eleven fragments, corresponding to transmembrane segments (TMs) of LacY, were synthesized, and their secondary structure in solution was determined by NMR. Eight of the TMs contained significant regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Similar observations were obtained in the simulation studies with ligand bound form of one of the well characterized MFS family members, LacY [58]. NMR studies have also shown that LacY domain D2 secondary structure is more stable than that of domain D1 [59]. In our glucose-ATP bound form simulation, domain D2 exhibited a significant conformational rearrangement and is seen as elevated RMSD.…”
Section: Resultssupporting
confidence: 86%
“…Similar observations were obtained in the simulation studies with ligand bound form of one of the well characterized MFS family members, LacY [58]. NMR studies have also shown that LacY domain D2 secondary structure is more stable than that of domain D1 [59]. In our glucose-ATP bound form simulation, domain D2 exhibited a significant conformational rearrangement and is seen as elevated RMSD.…”
Section: Resultssupporting
confidence: 86%
“…In at least one case , helix formation by an isolated TM segment could hence be shown to be independent of flanking hydrophilic residues (however, see Sections 3.2 and 5.2 for examples where this is not the case). More generally, organic solvents have proven useful in exploring the structural influence of tags (Tomich et al, 1998;Cano-Sanchez et al, 2006), comparing relative helical propensities of different peptides derived from the same membrane protein (Wigley et al, 1998;Lazarova et al, 2004;Bennett et al, 2006), and assessing the impact of disease-related mutations on TM peptide structure (Xie et al, 2000). In the latter case, the authors found that a TM peptide derived from a constitutively active mutant receptor displays a higher helical content than the wild-type peptide.…”
Section: Structure and Oligomerization Of Tm Peptides In Organic Solvmentioning
confidence: 99%
“…These focused on helix dynamics and stability,17 substrate binding,18; 19; 20; 21 and substrate transport pathway 1921; 22 Yin et al19 were the first to report any structural changes in LacY using a simulation approach.…”
Section: Introductionmentioning
confidence: 99%